PENGARUH TAKARAN VINASE DAN MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL WIJEN (Sesamum indicum L.) PADA TANAH PASIR PANTAI - , HENI SEPTIA PURWANINGSIH, Ir. Sri Muhartini, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Coastal sandy soil in southland of Yogyakarta is currently used for agriculture. Organic matter addition is needed to repair the problems in sandy soil. The research was aimed to study the effect of vinasse and manure and their interaction to sesame growth and yield. The research has been done from May until September 2013 at Wonocatur, Banguntapan, Bantul. Treatment which consisted of two factors (vinasse rate and kind of manure) with three replications were arranged in Randomized Completely Block Design (RCBD). The first factor was vinasse rates, i.e. 0 l/ha (without vinasse), 50.000 l/ha, 100.000 l/ha, and 150.000 l/ha. The second factor was three kinds of manure consisted of cow manure, poultry manure, and without manure. The result showed that the application of vinasse 150.000 l/ha increased roots length, number of leaf, shoot fresh weight, number of pod, seed weight per plant and yield. Adding vinasse up to 100.000 l/ha was not able to increase sesame growth and yield. Cow manure increased growth and yield of sesame.